The road half traveled : university engagement at a crossroads - Hodges, Rita Axelroth (Transformations in higher education., 2012)
A growing number of universities are dedicating resources to support their surrounding communities, but much potential for advancement remains. A university's mission as an "anchor institution," as defined by the authors, is to consciously and strategically apply the institution's long-term, place-based economic power, in combination with its human and intellectual resources, to better the welfare of the community in which it resides. Drawing on ten diverse universities as case studies, this eye-opening book explores practices and strategies that can be employed to improve condition.